2021
DOI: 10.3389/fcell.2021.729076
|View full text |Cite
|
Sign up to set email alerts
|

Rho Signaling in Synaptic Plasticity, Memory, and Brain Disorders

Abstract: Memory impairments are associated with many brain disorders such as autism, Alzheimer’s disease, and depression. Forming memories involves modifications of synaptic transmission and spine morphology. The Rho family small GTPases are key regulators of synaptic plasticity by affecting various downstream molecules to remodel the actin cytoskeleton. In this paper, we will review recent studies on the roles of Rho proteins in the regulation of hippocampal long-term potentiation (LTP) and long-term depression (LTD),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 181 publications
0
38
0
Order By: Relevance
“…This latter is emerging as a key regulator of nervous system physiology also involved in nervous system diseases and injury [ 122 ]. Moreover, pathways directly connected with ASD are: “Long term depression” that, together with “Long-term potentiation”, are the key regulators of long-lasting synaptic plasticity at the basis of learning and memory and whose impairment is involved in many brain disorders, including ASD [ 123 , 124 ]; “Insulin signalling pathway” promotes neuronal circuit development and maturation to an extent that, since its safety/preliminary efficacy for the treatment of Rett syndrome has emerged, clinical trials to ameliorate ASD symptoms are ongoing [ 125 ].…”
Section: Discussionmentioning
confidence: 99%
“…This latter is emerging as a key regulator of nervous system physiology also involved in nervous system diseases and injury [ 122 ]. Moreover, pathways directly connected with ASD are: “Long term depression” that, together with “Long-term potentiation”, are the key regulators of long-lasting synaptic plasticity at the basis of learning and memory and whose impairment is involved in many brain disorders, including ASD [ 123 , 124 ]; “Insulin signalling pathway” promotes neuronal circuit development and maturation to an extent that, since its safety/preliminary efficacy for the treatment of Rett syndrome has emerged, clinical trials to ameliorate ASD symptoms are ongoing [ 125 ].…”
Section: Discussionmentioning
confidence: 99%
“…While CA RhoA decreases spine length in mouse and rat hippocampal neurons, the effects of RhoA inhibition on spine morphology are less clear. DN RhoA increased spine length and reduced spine density in rat hippocampal neurons, increased spine density and spine length in mouse hippocampal neurons, and did not influence spine density in pyramidal neurons from rat hippocampal slices (Nakayama et al, 2000;Tashiro et al, 2000;Pilpel and Segal, 2004;Tashiro and Yuste, 2004;Impey et al, 2010;Murakoshi et al, 2011;Orefice et al, 2016;Zhang et al, 2021). These discrepancies may be caused by differences in neuron age, type, local levels of activity, definitions used for what constitutes dendritic spines, or distinctions in the extent of cell contact with other neurons or glia arising from non-equivalent plating densities (Govek et al, 2005).…”
Section: Rhoamentioning
confidence: 98%
“…Therefore, synapses are considered crucial for the developmental function of the nervous system (Bae & Kim, 2017 ; Batool et al, 2019 ; Selkoe, 2002 ; Skaper et al, 2017 ). Recent studies demonstrated that a range of neurological diseases could be characterized by the pathological changes in synapses, including abnormal dendritic spine morphology, synaptic loss, and destruction of synaptic plasticity (Zhang, Ben Zablah, et al, 2021 ). The synapse density can be reduced by 15%–35%, while the loss of synapses in the hippocampus of AD patients can reach as high as 44%–55% (Skaper et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%